Propuesta estratégica para el área de recursos humanos de Austral Group S.A.A. - Prado Rincón, Magaly Erika (2023)
Austral Group S.A.A. is part of the Norwegian group Austevoll Seafood ASA and is a recognized company in the fishing sector. It is the fifth largest exporter of fish flour and fish oil in Peru. Regarding the sale of fish flour, during 2022 they obtained higher average FOB export price domestically and that same year, they managed to diversify their customers for fishflour and fish oil. It has four production plants located in the most important ports on the coast of Peru, in Chimbote, Pisco, Ilo and Chancay. Of these, the Chimbote Plant is the largest, with a production of fish flour of 160 MT per hour and a production of frozen products of 599.45 MT per day. The present work carries out an evaluation of the company, from the business model, internal, external analysis, SWOT and application of a series of arrays that allowed to identify business opportunities. Accordingly, it identifies opportunities for improvement in the capture of raw materials, loyalty of third parties (Shipowners), strategic location that allow them to have a better capture in the business of indirect human consumption (CHI) and direct (CHD). The objective of this work is to propose the use of a balance scorecard, although sustainability reports show indicators aligned to the processes in the area, it is proposed to apply this methodology, to integrate all human resources components into the business strategy. Fishing is an opportunity business, by applying a balance scorecard, Human Resources becomes a strategic partner of the company.